Green manufacturing in garment industry through the application of fundamental lean tools. (9th December 2020) - Prabhu, N. Senthil; Rajenthirakumar, D.; Devadasan, S.R.; Gnanaguru, R.
In this paper, a model named as green through lean tools (GTLT) is proposed. GTLT was designed to implement green manufacturing in four phases through the adoption of three fundamental lean tools namely 5S, A3 Report and kaizen in garment manufacturing companies. The novelty of GTLT model is that the degree of implementing green manufacturing paradigm in the garment manufacturing company is assessed by using colours. Green colour refers to mean that green manufacturing paradigm has been fully implemented in the garment manufacturing company. After designing GTLT model, its practicality was examined in nine garment manufacturing companies. The results of this examination indicated that GTLT is an economical, powerful and practically feasible model that would enable the garment manufacturing companies to implement green manufacturing paradigm through the application of the above mentioned three fundamental lean tools.